The haunting of gay subjectivity: the cases of Oscar Wilde and John Marsden - D. Dalton (Law Text Culture, 2006)
I offer the juxtaposition of the two images opposite [see article] as a visual index of the arguments presented in this article. For I seek to address how notions of gay criminality are intricately connected in a nexus of history, cultural memory and the practices of naming and figuring, through which the past prevails to haunt the present. Consider figure 1. On the right hand side is an image of Oscar Wilde as he was sketched in court during his first (defamation) trial in London in 1895. On the left hand side is an image of a man named John Marsden — a photograph taken at the time of his 1999 defamation case in Sydney. His name does not accompany the image. Rather, by way of a substitute, the caption ‘The trial of an Australian Oscar Wilde’ dominates the cover. Both men are captured in profile; a perspective that Bertillon standardised as beneficial for archive purposes and one that is also used for ‘mugshots’. The juxtaposition of these two images invites judgment. The singularity of Wilde and his crimes is erased by the invocation of his name in relation to another man, John Marsden. The images perform an affiliation and confirmation. The wealth of criminality invested in the iconic figure of Oscar Wilde becomes a lens through which we can imagine the crimes of this man named as ‘an Australian Oscar Wilde’.